Impact response of tubular structure with internally stacked circular rings / Naziratie Assrinie Assan...[et al.] - Assan,, Naziratie Assrinie; Ab. Ghani, Amir Radzi; Ramly, Ramzyzan (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2019)
During collision, occupants and structures experience serious injuries and damages due to high impulsive force and poor impact energy absorption. Performance of energy absorption can be improved by selecting a suitable structure and material. A good crashworthiness structure should have low Initial Peak Force (IPF), high Crush Force Efficiency (CFE) and high Specific Energy Absorption (SEA). This paper introduces a new design that consists of stacked circular tubes within a square column which will be subjected to axial impact loading. The impact results were compared to static analysis of previous study in terms of IPF, CFE, SEA and DAF. Simulation results were validated by experiment before on embarking simulation parametric study. The experiment was conducted using the Drop Hammer Machine, Instron Dynatup 8250. Simulation results show good agreement with the experimental results. The increase in IPF and SEA were influenced by inertia compared to static at the same crush distance. Critical parameters were determined to give the best crushing performance among stacked tubes designs. From this study, it can be concluded that the best crushing performance depends on the dominant structure, amount of plastic hinge and structure stiffness.